Synthesis of Isonitriles from N-Substituted Formamides Using Triphenylphosphine and Iodine - Wang, Xia; Wang, Qing-Gang; Luo, Qun-Li (Synthesis, 2015)
Treatment of N-substituted formamides with the reagent combination of triphenylphosphine and molecular iodine, in the presence of a tertiary amine, quickly produces the corresponding isocyanides in high yields under ambient conditions. The process employs readily available and low-cost reagents, a convenient synthetic procedure, and mild reaction conditions for the synthesis of various alkyl and aryl isocyanides.
Keywords: isonitriles; formamides; dehydration; triphenylphosphine; iodine